Phytochemical characterization and antioxidant properties of the wild edible acerola Malpighia umbellata Rose. Issue 1 (1st January 2018) - Vasavilbazo-Saucedo, Andrés; Almaraz-Abarca, Norma; González-Ocampo, Héctor Abelardo; Ávila-Reyes, José Antonio; González-Valdez, Laura Silvia; Luna-González, Antonio; Delgado-Alvarado, Eli Amanda; Torres-Ricario, Rene
ABSTRACT: The objective of the current study was to determine the phenolic composition and carotenoid contents of leaves, bark, and fruits of Malpighia umbellata, assess the changes in the phenolic composition and contents of carotenoids and vitamin C of its fruits in different stages of maturity, and evaluate the antioxidant properties of its leaves, bark, and fruits. Leaves accumulated the highest levels of flavonoids (10.55 mg/g dry extract), tannins (21.16 mg/g dry extract), and carotenoids (424 63 µg/g dry tissue); whereas, the highest level of total phenolics was found in bark (47.12 mg/g dry extract). The vitamin C content decreased with the maturity of fruits. Twenty-two phenolics were characterized by high performance liquid chromatography with diode array detection (HPLC-DAD). Apigenin-7- O -glycosides, phenolic acids, and flavonols were predominant in leaves, bark, and fruits, respectively. Important chemical variations were found during fruit ripening. The 2, 2-diphenyl-1-picrylhydrazyl (DPPH ) scavenging activity and 2, 2ʹ-azino-bis-(3-ethylbenzothiazoline-6-sulfonic acid) (ABTS) inhibition assays revealed important antioxidant properties for this acerola.